2021
DOI: 10.1038/s41557-021-00788-x
|View full text |Cite
|
Sign up to set email alerts
|

A short peptide synthon for liquid–liquid phase separation

Abstract: The following full text is a publisher's version.For additional information about this publication click this link. https://repository.ubn.ru.nl/handle/2066/239188Please be advised that this information was generated on 2024-05-29 and may be subject to change. Article 25fa pilot End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
219
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(227 citation statements)
references
References 64 publications
7
219
1
Order By: Relevance
“…[113] The lab of Spruijt has recently reported coacervate microdroplets made of even smaller peptidic-based units. [114] They designed dipeptides from the hydrophobic amino acids phenylalanine (Phe) and leucine (Leu), which they joined together through the hydrophilic, disulfide-containing cystamine linker. The formation of micrometer size droplets was achieved by shifting the pH from 5À6 to 7.…”
Section: Artificial Polypeptide-based Simple Coacervatesmentioning
confidence: 99%
“…[113] The lab of Spruijt has recently reported coacervate microdroplets made of even smaller peptidic-based units. [114] They designed dipeptides from the hydrophobic amino acids phenylalanine (Phe) and leucine (Leu), which they joined together through the hydrophilic, disulfide-containing cystamine linker. The formation of micrometer size droplets was achieved by shifting the pH from 5À6 to 7.…”
Section: Artificial Polypeptide-based Simple Coacervatesmentioning
confidence: 99%
“…A large number of studies have shown that LLPS are formed in membraneless aggregates including nuclear spots and stress particles to maintain genome stability, transcriptional regulation, immune-related signal pathways, cellular stress response, cell proliferation, autophagy-related signal pathways, etc. ( Abbas et al, 2021 ; Guo et al, 2021 ; Peng et al, 2021 ; Su et al, 2021 ). Early research shows that abnormal LLPS plays a crucial role in the progression of neurodegenerative diseases ( Zbinden et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that some micro-compartments and protocell systems could compartmentalize (bio)chemical reactions, and act as catalytic microreactors or reaction localization centers with potential for prebiotic peptide ligation. [11][12][13][14][15][16] In particular, membraneless compartments based on complex coacervates have been considered as versatile protocell models in the origins of life research. 5,[16][17][18][19] Coacervate droplets are formed spontaneously by liquid-liquid phase separation, resulting in a polymer-or peptide-rich, cell-sized dense coacervate phase, and a coexisting dilute phase.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] In particular, membraneless compartments based on complex coacervates have been considered as versatile protocell models in the origins of life research. 5,[16][17][18][19] Coacervate droplets are formed spontaneously by liquid-liquid phase separation, resulting in a polymer-or peptide-rich, cell-sized dense coacervate phase, and a coexisting dilute phase. These membraneless droplets can easily take up and concentrate guest molecules from their surroundings due to charge complementarity or hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation